Model estimation of the whole life cost of a building with respect to risk factors - Wieczorek, Damian; Plebankiewicz, Edyta; Zima, Krzysztof (Technological and Economic Development of Economy, 2019)
The paper deals with estimating the life cycle cost and the whole life cost of a building. An original model for estimating the life cycle cost and the whole life cost of a building which allows the quantification of the increase in costs resulting from the incurred and assessed risk is presented. The proposed model consists of two basic parts: module I evaluating the impact of identified risk factors on individual element of the life cycle cost, and module II allowing to assess life cycle cost including the risk factors selected in module I. In module I the model of fuzzy inference of Mamdani was used. The structure of module II is based on the theory of possibilities and fuzzy sets. The operation of the model is presented on the example of an office building.